2001
DOI: 10.1021/jp011597n
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of the Lithium Interaction with Polycyclic Aromatic Hydrocarbons

Abstract: We have performed first-principles calculations in order to understand the binding mechanism of Li atoms in disordered carbon materials that are used for negative electrodes of rechargeable lithium batteries. We used pyrene, anthracene, and phenanthrene molecules as parts of disordered carbon. We examined several binding sites for two Li atoms in these aromatics and found that they are bound with substantial negative binding energies. The most negative one was -142.8 kJ/mol for Li-containing pyrenes, -211.0 kJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…The most sophisticate calculations were carried out recently on relatively small aromatic hydrocarbons [3]. In this work we investigate the comparably larger HBC using the hybrid B3LYP functional [9] with the 6-31G Ã basis set.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most sophisticate calculations were carried out recently on relatively small aromatic hydrocarbons [3]. In this work we investigate the comparably larger HBC using the hybrid B3LYP functional [9] with the 6-31G Ã basis set.…”
Section: Resultsmentioning
confidence: 99%
“…In this work we investigate the comparably larger HBC using the hybrid B3LYP functional [9] with the 6-31G Ã basis set. This method was shown to provide results comparable with M€ oller Plesset perturbation theory to second order (MP2) calculations [3]. We considered the interaction of two lithium atoms with the PAH and explored more than 20 combinations of interaction sites corresponding to configurations with both lithium atoms on the same side of the PAH or with the two lithium atoms on opposite sides of the PAH surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tight binding calculations showed that a flat band, composed of side edge carbon atoms, is located near the Fermi level [33]. Ab initio calculations for the interaction of the lithium atom with graphite model clusters indicated that charge transfer from the Li atom to the graphite cluster is important in large-cluster size [34][35][36][37]. But properties of Nano-scrolls and edge effects on graphene need wider studies [14].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] For Li-PAH neutral complexes, semiempirical computer simulations by Papanek et al showed that the high capacity of Li uptake by PAH molecules (Li atomic percent with respect to the number of carbon atoms) is partially attributable to Li binding at the hydrogen-terminated edges of pyrene, coronene, and several other PAH molecules, with local geometries analogous to the stable isomer of the organolithium molecule C 2 H 2 Li 2 . Interactions between Li/Li + and PAH molecules have been studied by many computational calculations.…”
Section: Introductionmentioning
confidence: 99%